Enantioselective dioxytosylation of styrenes using lactate-based chiral hypervalent iodine(III) - Fujita, Morifumi; Miura, Koki; Sugimura, Takashi (Beilstein Journal of Organic Chemistry, 2018)
A series of optically active hypervalent iodine(III) reagents prepared from the corresponding (R)-2-(2-iodophenoxy)propanoate derivative was employed for the asymmetric dioxytosylation of styrene and its derivatives. The electrophilic addition of the hypervalent iodine(III) compound toward styrene proceeded with high enantioface selectivity to give 1-aryl-1,2-di(tosyloxy)ethane with an enantiomeric excess of 70–96% of the (S)-isomer.
Keywords: 1,2-difunctionalization of alkenes; enantioselective synthesis; hypervalent iodine; oxidation